Development of Spectrophotometric Method for Analysis of Framicetine Sulphate in a Medicinal Product and its Validation - Gapparov Dilshodbek Davronbekovich1, Smanova Zulaykho Asanalievna2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A procedure for the quantitative determination of framycetin sulfate in the drug ‘Framex’ (nasal spray) 8000IU/ml has been developed, using spectrophotometry (SF) method. The developed method has been validatedusing the following indicators: specificity, correctness, linearity, repeatability and intralaboratory accuracy.It has been found that the developed methodology is valid for all characteristics and can be used for thequantitative determination of framycetin sulfate in the substances and composition of medicinal products.